What drives cloud ERP continuance? An integrated view. Issue 5 (10th August 2018) - Cheng, Yung-Ming
Abstract : Purpose: The purpose of this paper is to explore the key antecedents of organizational users' continuance intention of cloud enterprise resource planning (ERP) by the integration of constructs from the expectation–confirmation model (ECM), technology acceptance model (TAM), theory of planned behavior (TPB), task-technology fit and TAM2. Design/methodology/approach: Sample data for this study were collected from end users of cloud ERP working in companies in Taiwan. A total of 560 questionnaires were distributed in the 56 sample companies, and 395 (70.5 percent) usable questionnaires were analyzed using structural equation modeling in this study. Findings: Findings show that while compatibility and output quality are key antecedents of confirmation of expectations toward cloud ERP, compatibility still reveals overwhelming and more indirect impacts on users' continuance intention of cloud ERP than output quality because output quality has significant but evidently lesser effects on perceived usefulness and perceived ease of use than compatibility. Originality/value: First, this study contributes to the identification of compatibility and output quality that may reveal deep insights to the task-related factors in understanding users' cloud ERP continuance greatly driven by their confirmation of expectations toward cloud ERP. Next, the empirical evidence on capturing the ECM, TAM and TPB for completely explaining the antecedents of users' continued cloud ERP usage intention is well documented. Hence, this study's findings have significantly shed light on the possible formulation of a richer post-adoption model.